EXPLORING GENDER DIFFERENCES IN THE DETERMINANTS OF CROP PRODUCTION TECHNOLOGY USE IN AKKO LOCAL GOVERNMENT AREA OF GOMBE STATE, NIGERIA - Salihu, A.; Musa, A.T.; Ahmed, M.A.; Aliyu, B. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
This study investigated the gender differences in the determinants of crop production technology use among farmers in Akko Local Government Area, Gombe State, Nigeria. The specific objectives were to describe the socioeconomic characteristics of the respondents, ascertain the factors influencing their use of crop production technologies, and identify the constraints associated with adoption of crop production technologies. A multistage sampling procedure was used to select 248 respondents, and data were analyzed using descriptive statistics and multiple regression analysis. The results showed that male farmers had larger mean household sizes (7 persons) than females (5 persons), and higher levels of formal education, with 70.84% of males attaining at least primary education compared to 54.90% of females. Multiple regression analysis revealed that age (P<0.01), education status (P<0.05), and farming experience (P<0.10) of male farmers significantly influenced their crop production technology usage, with the model explaining 85.82% of the variation. For female farmers, farming experience was the only significant determinant (P< 0.01), accounting for 64.17% of the variation in technology usage. Major constraints affecting both male and female farmers included lack of awareness (male = 2.46; female = 2.47), high cost of technology (male = 2.56; female = 2.72), low literacy levels (male = 2.57; female = 2.60), and inadequate extension contacts (male = 2.49; female = 2.81). Difficult application procedures were a severe constraint for female farmers only (mean = 2.72). The study concluded that age, education status and farming experience were the determinants of crop production technology usage among male farmers in the study area while farming experience remains the only determinant among female farmers. It is recommended that information on available crop production technologies should be disseminated through multiple channels such as community meetings, radio programs, farmer groups, and mobile platforms to ensure both male and female farmers are adequately informed.